Clinical significance of regional lymph node enlargement in patients with EGC within the expanded criteria for ESD - Lee, Dong Seok; Park, Jong Kyu; Lee, Sang Jin; Cheon, Gab Jin (BMC gastroenterology, 2020)
s Background Lymph node (LN) metastasis is negligible in early gastric cancer (EGC) within expanded criteria for endoscopic submucosal dissection (ESD). However, regional lymph nodes in abdominal CT scans are sometimes enlarged in patients with EGC within the expanded criteria for endoscopic submucosal dissection (ESD). In this study, we investigated the clinical significance of regional lymph node enlargement on abdominal CT scan in patients with EGC within the expanded criteria for ESD. Methods From December 2010 to April 2015, among 301 patients with EGC within the ESD expanded criteria, 47 patients with regional lymph node enlargement shown by abdominal CT scan were prospectively enrolled. We performed surgical resection or periodic follow-up with abdominal CT scans and upper endoscopy every 6 months to evaluate whether the enlarged lymph nodes are due to metastasis or a reactive change. Results The mean age of the 47 patients (38 males, 9 female) was 64.8 years. The enlarged lymph nodes were usually single (26/47, 44.6%) and sized as follows: 11 nodes were ≤ 5 mm, 19 were 6–10 mm, and 17 were ≥ 10 mm. Four of the 47 patients initially underwent surgical resection, and 8 patients underwent surgical resection after ESD. However, there was no lymph node metastasis in surgical specimens. Thirty-five patients received ESD and periodically followed up at a median duration of 56 months (IQR: 44–59 month). The enlarged lymph node disappeared in 12 of 35 patients, decreased in 9 patients and remained the same size in 13 patients, and increased in 1 patient. Conclusion Regional lymph node enlargement on abdominal CT scan in patients within expanded criteria for ESD of ECG may be not due to metastasis but a reactive change.